GROWTH AND PHYSIOLOGY OF PANICUM SPECIES FOR THERMOTOLERANCE UNDER HYDROPONIC CONDITIONS - M. A. Wasim; R. M. Iqbal; M. Akram (Journal of Animal and Plant Sciences, 2013)
Experiment for study of growth and physiology of the three Panicum species (Panicum coloratum, Panicum antidotale and Panicum maximum) was conducted under self made hydroponic system at The Cholistan Institute of Desert Studies, The Islamia University of Bahawalpur, Pakistan. Three different panicum species and four treatments (Thermopore sheet thickness) to control the escape of heat from the pots were used in the study. One week older seedling of panicum were uprooted and transplanted in the hydroponics solution culture with thermopore sheet and each plant was supported with the help of foam and their roots immersed in plastic pot containing modified nutrient Solution. The experiment was laid out in completely randomized design and replicated three times. Main tiller length, number of leaf per plant, number of tiller, leaf area, fresh weight and dry weight per plant measured in all the three different Panicum species at different temperature levels were recorded. The result indicated that Panicum species gained maximum main tiller length, number of leaf and tiller per plant, leaf area, fresh and dry weight per plant at T3 treatment, where hydroponic root temperature was reduced by using one and half inches thermopore sheets. But at control treatment whose root temperature shoots up to 50˚C, minimum growth was observed. Among different Panicum species Panicum coloratum was the better adapted to tolerate high water temperature in hydroponic culture than other Panicum species by gaining maximum tiller length, fresh and dry weight, thus proved to be tolerant of high temperature.
Keywords: Panicum species; main tiller length; fresh weight; chlorophyll contents